Féminismes et pornographie - Courbet, David (La Musardine, 2012)
Comment le féminisme peut se reconnaître dans la pornographie Objet de débats où la passion l'emporte bien souvent sur la raison, la pornographie semble à première vue s'opposer au féminisme. Or, les années 1980 voient éclore aux Etats-Unis un courant se définissant comme " pro-sexe " porté par des figures telles Annie Sprinkle ou Candida Royalle. Avec l'idée que la pornographie n'est pas systématiquement condamnable, la question suivante s'impose : peut-on parler de moyen d'émancipation ? La femme doit être libre de choisir la sexualité qui lui convient. Les films pornographiques conçus par des hommes et pour des hommes ne lui permettant pas d'obtenir une satisfaction complète, des réalisatrices, parmi lesquelles Erika Lust, Ovidie ou Emilie Jouvet, promeuvent une pornographie alternative où le plaisir féminin est - enfin - mis en exergue. Et brisent les standards pornographiques dominants ! Peu étudiées en France, les thèses défendues par les féministes pro-sexe n'ont encore que peu d'échos au sein du grand public. Basé notamment sur une dizaine d'entretiens de spécialistes et professionnels, ce travail cherche à élucider en quoi le féminisme peut se reconnaître dans la pornographie. Et inversement.
Section: 1 vol. (276 p.) : couv. ill. en coul. ; 19 cm.
Keywords: approches et analyses; corps; cours; discipline; féminisme pop; féminisme pro-sexe; journalisme; premier cycle; science politique; science politique et droit; sciences humaines; sex1911; sexologie; sexualité; thématiques; travail

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

Anti-porn: the resurgence of anti-pornography feminism - Long, Julia (Zed Books, 2012)
"Anti-porn feminism is back. Countering the ongoing 'pornification' of Western culture and society, with lads' mags on the middle shelf and lap-dancing clubs in residential areas, anti-porn movements are re-emerging among a new generation of feminist activists worldwide. This essential new guide to the problems with porn starts with a history of modern pro and anti political stances before examining the ways in which the new arguments and campaigns around pornography are articulated, deployed and received. Drawing on original ethnographic research, it provides an in-depth analysis of the groups campaigning against the pornography industry today, as well as some eye-opening facts about the damage porn can do to women and society as a whole. This unique and inspiring book explains the powerful comeback of anti-porn feminism, and it controversially challenges liberal perspectives and the mainstreaming of a porn culture that threatens to change the very nature of our intimate relationships"–Résumé de l'éditeur.
Section: 246 p. ; 23 cm
Keywords: approches et analyses; corps; cours; discipline; féminisme anti-porn; féminisme pop; militance; patriarcat; premier cycle; sex1911; sexualité; systèmes d'oppressions; thématiques